Effect of Oral Clonidine Premedication on Hemodynamic Stress Response to Laryngoscopy and Tracheal Intubation - Prasad, Jagat Narayan; Singh, Satendra Narayan; Sah, Suresh Prasad; Guddy, KM; Sarraf, Deependra Prasad (Birat Journal of Health Sciences, 2022)
Introduction: Different techniques have been tried to blunt undesirable hemodynamic effects like tachycardia, hypertension and dysarrhythmias during and after laryngoscopy and tracheal intubation. Objective: To find out the effect of oral clonidine premedication on hemodynamic stress response to laryngoscopy and tracheal intubation. Methodology: It was a prospective, randomized, double-blind comparative study conducted in patients undergoing laparoscopic cholecystectomy. Either oral clonidine 300 mcg (n=30) or placebo (n=30) was given one hour before the surgery. Depth of anesthesia was monitored and maintained at 40-60 level using bispectral index (BIS) monitor. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial blood pressure (MABP) and oxygen saturation (SpO2) at baseline, one hour after premedication, on operation theatre (OT) table, just before and after one, two and five minutes after laryngoscopy and intubation were compared in Clonidine and placebo group using Paired t test and Chi-square test. SPSS was used for statistical analysis at P-value<0.05 Results: Hemodynamic variables like HR, SBP, DBP and MBP were significantly lower in the clonidine group compared to placebo just before and after the first five minutes of laryngoscopy and tracheal intubation (P<0.05). Propofol requirement for induction of anesthesia was less in the clonidine group (95±31.8 mg vs 75.3±28.5 mg, p=0.014) compared to the placebo group. Adverse effects like hypotension and bradycardia were comparable in the groups. Time taken for extubation, time to follow verbal commands and time to orientation after surgery were similar in the both groups (P>0.05). Conclusion: Oral clonidine premedication was effective in blunting undesirable hemodynamic stress response to laryngoscopy and tracheal intubation compared to the placebo.